2013
DOI: 10.1017/s1751731112001176
|View full text |Cite
|
Sign up to set email alerts
|

The decrease in milk yield during once daily milking is due to regulation of synthetic activity rather than apoptosis of mammary epithelial cells in goats

Abstract: Once daily milking (ODM) is a management practice that can improve working conditions and reduce production costs in dairy farming compared with twice daily milking (TDM). However, ODM is associated with a decrease in milk yield. Previous research indicated that disruption of tight junctions in the mammary gland may be one of the regulatory factors involved in the milk yield decrease observed during ODM. The aim of this study was to investigate the involvement of mammary epithelium disruption in the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
18
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 28 publications
3
18
0
1
Order By: Relevance
“…The expression of LALBA increases upon treatment with a cocktail of lactogenic hormones (i.e., insulin ϩ hydrocortisone ϩ prolactin ϩ 17␤-estradiol or growth hormone), as observed in mouse and bovine mammary cells in vitro (105,199). The expression of LALBA is also induced by increased milking frequency in bovine and caprine (21,154) and by the AA Lys and Met in primary bovine mammary cells (155), but it is decreased by mastitis in dairy cow and yak (126,150) and by feed restriction in the cow (62). It is well established that the promoter region of LALBA contains a STAT5 binding site, and the presence of STAT5 is essential for the expression of LALBA in mouse (178,245).…”
Section: Transcriptional Regulation Of the Lactose Synthase Enzymes Lmentioning
confidence: 90%
“…The expression of LALBA increases upon treatment with a cocktail of lactogenic hormones (i.e., insulin ϩ hydrocortisone ϩ prolactin ϩ 17␤-estradiol or growth hormone), as observed in mouse and bovine mammary cells in vitro (105,199). The expression of LALBA is also induced by increased milking frequency in bovine and caprine (21,154) and by the AA Lys and Met in primary bovine mammary cells (155), but it is decreased by mastitis in dairy cow and yak (126,150) and by feed restriction in the cow (62). It is well established that the promoter region of LALBA contains a STAT5 binding site, and the presence of STAT5 is essential for the expression of LALBA in mouse (178,245).…”
Section: Transcriptional Regulation Of the Lactose Synthase Enzymes Lmentioning
confidence: 90%
“…In such samples, the expression of genes related to milk production and mammary gland physiology may not provide a true representation (14). Comparatively, milk enriched MEC can be a potential and noninvasive alternative to biopsies from mammary tissues for studying cell specific expression of key genes associated with lactation (13,15) and provide a more precise reflection of mammary gland for studies related to milk synthesis (16)(17)(18)(19)(20)(21). Riverine buffalo (Bubalus bubalis) is a major milk producing species in many Asian and Mediterranean countries and its genetic improvement ranks high among agricultural research needs of these countries.…”
Section: Expression Profiling Of Glucose Transporter 1 (Glut1) and Apmentioning
confidence: 99%
“…The rate of cell proliferation and apoptosis are the key processes that maintain equilibrium of MEC in the mammary gland during lactation (10,27). The expression of BAX and BCL2 genes and BAX=BCL2 ratio were calculated as indicative of the apoptotic rate in MEC harvested at different time points of lactation (1,14,21). Furthermore, BAX and BCL2 expression in milk MEC had been correlated with the decrease in milk yield during daily milking (13,21,22 (Fig.…”
Section: Expression Of Glut1 and Apoptotic Genes In Mec 155mentioning
confidence: 99%
“…Moreover a comparison of gene expression in both mammary tissue and milk-purified MEC has only been performed for a small number of genes: essentially coding for milk proteins and stearoyl-CoA desaturase (SCD) (4, 13, 25, 36). Our previous study showed a downregulation of ␣-lactalbumin (LALBA) transcripts after ODM in both milk-purified MEC and tissue samples from goats (4).…”
mentioning
confidence: 96%
“…By contrast, apoptosis has been studied in goat mammary tissue but inconsistent results were obtained. Indeed, whereas apoptosis was demonstrated in one study (33), two others did not observe apoptosis when examined by terminal deoxynucleotidyl transferase-mediated 2=-deoxyuridine 5=-triphosphate nick-end labeling (TUNEL) staining (4,11). Furthermore, it is unknown whether ODM affects mammary cell proliferation.…”
mentioning
confidence: 99%